Utilizing Social Networks as Learning Tools to Transform Education - Dejan Antonio (GoAcademica Research & Publishing, 2022)
Collaborative learning is made possible through the use of technological communication networks, which provide information sharing places to encourage teamwork. There is a growing trend in colleges across Spain and Latin America, especially in Mexico, to use social networks, one of the most emblematic Web 2.0 tools, to teach students about the history and appeal of the Internet. There was a research done with 414 students from the 14 majors provided at the University of Guadalajara's Los Altos University Center to investigate the efficacy of social networking as a means of education. Seventy-one percent of respondents said they use them for school-related activities; 45 percent use them to study; and 42 percent use them to play, all of which highlights the growing role and influence that social networks are playing in the classroom.